Differential Modulation of Ethanol-Induced Sedation and Hypnosis by Metabotropic Glutamate Receptor Antagonists in C57BL/6J Mice - Sharko, Amanda C. (2007)
BACKGROUND: Emerging evidence implicates metabotropic glutamate receptor (mGluR) function in the neurobiological effects of ethanol. The recent development of subtype specific mGluR antagonists has made it possible to examine the roles of specific mGluRs in biochemical and behavioral responses to ethanol. The purpose of the present study was to determine if mGluRs modulate the acute sedative-hypnotic properties of ethanol in mice. METHODS: C57BL / 6J mice were tested for locomotor activity (sedation) and duration of loss of the righting reflex (hypnosis) following acute systemic administration of ethanol alone or in combination with the mGluR5-selective antagonist, 2-methyl-6-(phenylethynyl)pyridine (MPEP), the mGluR1-selective antagonist, 7-(hydroxyimino)cyclopropa[b]chromen-1a-carboxylate ethyl ester (CPCCOEt), or the mGluR2 / 3-selective antagonist (2S)-2-Amino-2-[(1S,2S)-2-carboxycycloprop-1-yl]-3-(xanth-9-yl) propanoic acid (LY341495)). RESULTS: MPEP (10 and 30 mg / kg) significantly enhanced both the sedative and hypnotic effects of ethanol, while LY341495 (10 and 30 mg / kg) significantly reduced the sedative-hypnotic effects of ethanol. CPCCOEt had no effect at any concentration tested. Further loss of righting reflex experiments revealed that LY341495 (30 mg / kg) significantly reduced hypnosis induced by the gamma-aminobutyric acid type A (GABAA) positive modulators, pentobarbital (50 mg / kg) and midazolam (60 mg / kg), and the N-methyl-D-aspartate (NMDA) receptor antagonist, ketamine (150 mg / kg), while MPEP (30 mg / kg) only significantly enhanced the hypnotic properties of ketamine (150 mg / kg). CONCLUSIONS: These findings suggest that specific subtypes of the metabotropic glutamate receptor differentially modulate the sedative-hypnotic properties of ethanol through separate mechanisms of action, potentially involving GABA(A) and NMDA receptors.